Application of Vigenere Cipher to Enhance the Playfair Cipher Security - Gupta, Prachi; Kumar, Manoj (International Journal of Psychosocial Rehabilitation, 2020)
We present a new approach for secure transmission of message by modified version of Playfair cipher with Random number generator methods combining with Vigenere cipher. To develop this method of encryption technique, one of the simplest methods of random number generator methods called linear congruential generator has been used. Playfair cipher method based on polyalphabetic cipher. It is relatively easy to break because it still leaves much of the structure and a few hundred of letters of ciphertext are sufficient. In this we used double encryption and decryption technique. For the encryption, first encrypt the plaintext by vigenere cipher, and then result encrypt by playfair cipher. And result is called ciphertext. After that we are mapping random numbers to ciphertext and corresponding numbers will be transmitted to the recipient instead of alphabetical letter. This method rapidly increases security of the transmission over an unsecured channel.